The Deciphering of Growth-Dependent Strategies for Quorum-Sensing Networks in Pseudomonas aeruginosa - Juříková, Tereza; Mácha, Hynek; Lupjanová, Vanda; Pluháček, Tomáš; Marešová, Helena; Papoušková, Barbora; Luptáková, Dominika; Patil, Rutuja H; Benada, Oldřich; Grulich, Michal; Palyzová, Andrea (Microorganisms, 2023)
Pseudomonas aeruginosa is recognized as a significant cause of morbidity and mortality among nosocomial pathogens. In respiratory infections, P. aeruginosa acts not only as a single player but also collaborates with the opportunistic fungal pathogen Aspergillus fumigatus. This study introduced a QS molecule portfolio as a potential new biomarker that affects the secretion of virulence factors and biofilm formation. The quantitative levels of QS molecules, including 3-o-C12-HSL, 3-o-C8-HSL, C4-HSL, C6-HSL, HHQ, PQS, and PYO, measured using mass spectrometry in a monoculture, indicated metabolic changes during the transition from planktonic to sessile cells. In the co-cultures with A. fumigatus, the profile of abundant QS molecules was reduced to 3-o-C12-HSL, C4-HSL, PQS, and PYO. A decrease in C4-HSL by 50% to 170.6 ± 11.8 ng/mL and an increase 3-o-C12-HSL by 30% up to 784.4 ± 0.6 ng/mL were detected at the stage of the coverage of the hyphae with bacteria. Using scanning electron microscopy, we showed the morphological stages of the P. aeruginosa biofilm, such as cell aggregates, maturated biofilm, and cell dispersion. qPCR quantification of the genome equivalents of both microorganisms suggested that they exhibited an interplay strategy rather than antagonism. This is the first study demonstrating the quantitative growth-dependent appearance of QS molecule secretion in a monoculture of P. aeruginosa and a co-culture with A. fumigatus.
Keywords: Aspergillus fumigatus; QS system; metabolomic analysis; microbial interaction; biofilm; Pseudomonas aeruginosa; planktonic cell